Proteomic analysis of cardiac ventricles: baso-apical differences - Eckhardt, Adam; Kulhava, Lucie; Miksik, Ivan; Pataridis, Statis; Hlavackova, Marketa; Vasinova, Jana; Kolar, Frantisek; Sedmera, David; Ostadal, Bohuslav (Molecular and cellular biochemistry, 2018)
The heart is characterized by a remarkable degree of heterogeneity. Since different cardiac pathologies affect different cardiac regions, it is important to understand molecular mechanisms by which these parts respond to pathological stimuli. In addition to already described left ventricular (LV)/right ventricular (RV) and transmural differences, possible baso-apical heterogeneity has to be taken into consideration. The aim of our study has been, therefore, to compare proteomes in the apical and basal parts of the rat RV and LV. Two-dimensional electrophoresis was used for the proteomic analysis. The major result of this study has revealed for the first time significant baso-apical differences in concentration of several proteins, both in the LV and RV. As far as the LV is concerned, five proteins had higher concentration in the apical compared to basal part of the ventricle. Three of them are mitochondrial and belong to the "metabolism and energy pathways" (myofibrillar creatine kinase M-type, L-lactate dehydrogenase, dihydrolipoamide dehydrogenase). Myosin light chain 3 is a contractile protein and HSP60 belongs to heat shock proteins. In the RV, higher concentration in the apical part was observed in two mitochondrial proteins (creatine kinase S-type and proton pumping NADH:ubiquinone oxidoreductase). The described changes were more pronounced in the LV, which is subjected to higher workload. However, in both chambers was the concentration of proteins markedly higher in the apical than that in basal part, which corresponds to the higher energetic demand and contractile activity of these segments of both ventricles.
Keywords: Animals; Muscle Proteins; 2D gelová elektroforéza; Heart Ventricles; Rats, Wistar; svalové proteiny; kreatinkinasa, forma MM; srdeční komory; Tandem Mass Spectrometry; energetický metabolismus; chaperon hsp60; proteomika; Electron Transport Complex I; respirační komplex I; Chromatography, Liquid; Energy Metabolism; mitochondriální proteiny; dihydrolipoamiddehydrogenasa; lehké řetězce myosinu; Myosin Light Chains; Proteomics; L-Lactate Dehydrogenase; Chaperonin 60; tandemová hmotnostní spektrometrie; Male; Electrophoresis, Gel, Two-Dimensional; L-laktátdehydrogenasa; Creatine Kinase, MM Form; Mitochondrial Proteins; zvířata; mužské pohlaví; Dihydrolipoamide Dehydrogenase; chromatografie kapalinová; potkani Wistar